The mechanism of use of innovations in crisis management - S. S. Shirokov (Путеводитель предпринимателя)
Mechanism of crisis management through innovation organizations at different stages of the crisis, is considered. Signs for the classification of companies at different stages of the crisis offered. Model of select of the class organizations, at different stages of the crisis, developed.